Dehumanization and Oppression of Females in Achebe’s “Things Fall Apart” - Dr. Fahim Cheffat Salman, (Indian Journal of Social Science and Literature (IJSSL), 2024)
African literature with its great reputation starts as an oral literature to a form of literature that is written in the languages of colonizers. It reveals many powerful cultural and political frameworks that impress to maintain displacement intact. Culture as a complicated social apparatus and regulation. This paper reveals dehumanization and oppression of females in the black continent. The place of women in Igbo cultural practices is depicted by Chinua Achebe in his famous book Things Fall Apart by highlighting the significant and vital role Igbo women play in the story. This was achieved by a thorough analysis of the book. depends on the important roles that women play in education, religion, society, and other spheres, as understood from the book. The conclusion of the essay is that women’s status in Igbo culture is essential and fundamental to the survival of human civilization.